CITRA GENDER PEREMPUAN-PEREMPUAN TAHANAN POLITIK INDONESIA MASA ORDE BARU DALAM NOVEL DARI DALAM KUBUR - Iswan Afandi (Widyaparwa, 2022)
The purpose of this study is to describe the image of Indonesian women political prisoners in the novel Dari Dalam Kubur. This type of research uses qualitative research with descriptive methods. The theory used in this research is the theory of feminism. The analysis focuses on the author's thoughts, social phenomena, and traditional and modern culture about women, including marginalization, stereotypes, subordination, violence, and workload. There are different types of feminism. Therefore, the type of feminism presented in the study is adjusted to the research findings. Data was collected, through library data sources, and relevant research journal articles. The data collection technique used in this research is the reading and note-taking technique. The novel is read in its entirety and then recorded things that are by the research focus. The results showed that the type of feminism used by the author of Marching was socialist-Marxist feminism. Something is interesting in the research findings, namely the phenomenon of "intellectual genocide" through the application of the "spatial organization" method by the New Order government to kill groups of women who are considered to have "left ideology" in Indonesia. In addition, there was a colonial transformation into a neocolonial culture, in which Indonesian women were socially and politically colonized by the United States and the New Order rulers. Problems of gender inequality were found, namely the problem of violence against women, marginalization, stereotypes, subordination, and double workload.Tujuan penelitian ini adalah mendeskripsikan citra perempuan tahanan politik Indonesia dalam novel Dari Dalam Kubur. Jenis penelitian ini menggunakan penelitian kualitatif dengan metode deskriptif. Teori yang digunakan dalam penelitian, yaitu teori feminisme. Analisis difokuskan pada pemikiran pengarang, fenomena sosial, budaya tradisional dan modern tentang perempuan, meliputi marginalisasi, stereotipe, subordinasi, kekerasan, dan beban kerja. Ada berbagai jenis-jenis feminisme. Oleh karena itu, jenis feminisme yang disajikan dalam penelitian disesuaikan pada temuan penelitian. Data yang dikumpulkan, melalui sumber data perpustakaan, artikel jurnal penelitian yang relevan. Teknik pengumpulan data yang digunakan dalam penelitian ini ialah teknik baca dan catat. Novel dibaca keseluruhan kemudian dicatat hal-hal yang sesuai dengan fokus penelitian. Hasil penelitian menunjukkan jenis feminisme digunakan oleh pengarang Marching ialah feminisme sosialis-marxist. Ada yang menarik dalam temuan penelitian, yakni fenomena “genosida intelektual” melalui penerapan metode “pengorganisasian ruang” oleh pemerintah orde baru untuk membunuh kelompok perempuan yang dianggap memiliki “ideologi kiri” di Indonesia. Selain itu, terjadi transformasi kolonial ke budaya neokolonialisme, yakni perempuan Indonesia dijajah secara sosial dan politik oleh Amerika Serikat dan penguasa orde baru. Masalah ketidakadilan gender ditemukan yakni masalah kekerasan terhadap perempuan, marginalisasi, stereotipe, subordinasi, dan beban kerja ganda.